Master's piano recital - Kolesnikov, Inna (Kansas State University, 2007)
This Master's report encompasses analysis of the four works performed on November 14th, 2007 for the author's Master's recital. The analysis was based on the author's experience with the pieces. Many sources were utilized to discuss composers' biographies and background information of the works. The compositions are Ludwig van Beethoven's Piano Sonata in F major, Op.10, Franz Schubert's Sonata in A major, D. 664, Fryderyk Franciszek Chopin's Nocturne in F sharp major, Op. 15, and Sergei Prokofiev's Piano Sonata No.3 in A minor.
Keywords: Music; Piano; Recital; Beethoven; Schubert; Chopin; Music (0413)